Calcium regulation of transcription in plants - Fromm, Hillel (Henry Stewart Talks, 2012)
Calcium as a ubiquitous second messenger, Evolution and status in plant cells, Calmodulin as a transducer of Calcium signals, Mechanisms of transcription regulation by Calcium, Calmodulin-binding transcription activators, Calcium regulation of transcription in defense responses, CAMTA and regulation of growth and stress responses
Reviewed at 2020/08/12